Comparative Study of Motivation Attributes among Teachers at Cadet and Public Sectors Colleges - Muhammad Amjad, Shazia Zamir (PJE, 2023)
Motivation refers to a reason that motivates manners that is characterized by readiness and wish. This research was focused to compare the intrinsic and extrinsic motivation of teachers teaching in Cadet and Public sector colleges. The population of this study was comprised of all Cadet and Public Colleges of Khyber Pakhtunkhwa (Pakistan).One hundred teachers teaching in Cadet and Public sectors colleges included in the sample. Probability sampling technique was used to select sample of the study.